Recreation Opportunity Spectrum Analysis of Strategic Area Tourism Destination Pelang Region - Suksmawati, Herlina; Rahmatin, Leily Suci; Firdaus, Praja (E-Journal of Tourism; Volume 8 Number 2 (September 2021)DO - 10.24922/eot.v8i2.77562, 2021)
Tourism planning and development should be adjusted based on regional characteristics and applicable policies, but over time, tourism planning often pays less attention to the carrying capacity of the region. So there is a need for an analytical study of tourism planning that is tailored to the characteristics of the region to create sustainable tourism. This research was conducted at the Pelang Regional Tourism Destination, Trenggalek Regency using Recreation Opportunity Spectrum Analysis and the concept of Attractions, Amenities, Access, Ancillary to see tourism potential. The research methodology used is Qualitative Description with the methods of collecting observation data, documentation studies and in-depth interviews. Tourism development in the Pelang Regional Tourism Destinations based on regional tourism development planning is included in the concept of natural tourism development with collaborative management between stakeholders, but in the current development implementation when viewed from the Recreation Opportunity Spectrum analysis there is no clear management system and the Pelang Tourism Destinations are classified as the characteristics of semi-primitive areas have not paid attention to aspects of appropriate land use functions, especially in the development of tourism supporting infrastructure.